Cancer pain control: an evidence-based approach - Carr, Daniel; Tayeb, Baraa (Henry Stewart Talks, 2009)
Importance of cancer pain control, Assessment and sources of cancer pain, Selecting agents according to pain mechanism, The WHO ladder, Nonopioids and adjuvants, Opioids, Side effects, Neuraxial drug delivery, Nondrug modalities, What does the published evidence show?, Update talk: Changes in cancer pain control since 2009
Updated at 2021/11/30